Fruit and vegetable smoothies preservation with natural antimicrobials for the assurance of safety and quality - Nieva, S. G. (2021)
Current consumption trends indicate a clear increased interest in more natural, nutritious and healthier foods. Accordingly, natural fruits and vegetables (F&V) based beverages (juices, smoothies) companies showed great growth, since perceived as a practical way of ingesting the F&V nutrients and bioactives. However, when untreated, these products have a short shelf-life, mainly due to microbial spoilage. The combination of natural antimicrobials for their preservation constitutes an option in line with consumers’ requirements. This study aims to evaluate different combinations of natural antimicrobials, nisin, natamycin, green tea extract (GTE) and citric acid, to preserve the quality of a mixed F&V smoothie, extending their shelf-life and ensuring their safety. The results obtained suggest that a treatment with nisin 12.5 mg/kg natamycin 200 mg/kg and citric acid (until pH 3.5) could achieve a shelf-life extension of 14 d, a product with great nutritional and microbiological quality until 28 d of storage at 5 °C. Moreover, this treatment would allow controlling a 6 log CFU/mL Listeria monocytogenes contamination. Furthermore, if GTE (0.2%) is added to that combination, a product with fortified antioxidant properties (more than 10 times higher than control) is achieved, fulfilling the requirements of the most demanding natural products consumers.